Low Temperature Soft Chemical Synthesis of Bright Blue CoAl2O4 Spinel Particles - Stella, K. Christine; Nesara, A. Samson (Journal of Nepal Chemical Society, 2010)
Present work reports the preparation of bright blue CoAl2O4 spinel particles by low temperature soft chemical route using urea or glycine as fuel in this paper. The characterization of the resulting powder was done using x-ray diffraction (XRD), particle size analysis and scanning electron microscopic (SEM) techniques. Pure CoAl2O4 spinel particles were prepared at relatively low temperature using this soft chemistry route at a very short duration (< 10 minutes) which is also very simple than other techniques such as solid state reaction, ceramic methods and so on. From the particle size analysis, it was found that the spinel particles with low diameter (below 35 μm) were formed. The SEM photographs showed the formation of fluffy morphology with porous structure. Keywords: Cobalt aluminate spinel, low temperature soft chemistry route, XRD, SEM. DOI: 10.3126/jncs.v25i0.3302 Journal of Nepal Chemical Society Volume 25, 2010 pp 62-69